Pelatihan Bahasa Inggris Aktif Bagi Peserta Kejar Paket B Di Pusat Kegiatan Belajar Masyarakat (PKBM) Rinjani Kota Mataram Nusa Tenggara Barat - Etika Ariyani (Yayasan Kajian Riset dan Pengembangan RADISI, 2022)
Mastery of English is something that plays an important role in the era of globalization. The community service program was held to increase the quality of human resources through communicative English training for participants in the Kejar Package B at the Rinjani Community Learning Activity Center (PKBM), Kekalik Jaya Environment, Mataram City – West Nusa Tenggara. This training aims to provide active English skills for trainees so that later they can use these skills to get better jobs in the future. This training was attended by 20 participants and was held twice a week for 3 months. The learning methods applied in this training are games and discussions to identify the knowledge and skills needed. The lecture method is used during the learning process for vocabulary and grammar development in English. The achievement of this community service program can be seen from the increase in learning outcomes, the results in the first cycle of 60.71% increased significantly to 79.17% in the second cycle. Achievement indicators have been met 75%. The training participants looked very enthusiastic and happy to participate in this activity, it can be concluded that the English language training which is presented in a fun and communicative way can have a significant influence on the abilities of the trainees.